A Clockwork Freedom. (12th April 2018) - Sullivan, Marek
Abstract : The Production of American Religious Freedom by Finbarr Curtis. New York University Press, 2016. 240 pp. Pb. 28.00, ISBN-13: 9781479856763; Hb. 89.00, ISBN-13: 9781479882113.